Ghrelin and Obestatin Levels in End-stage Renal Disease - Aygen, B.; Dogukan, A.; Dursun, F. E.; Aydin, S.; Kilic, N.; Sahpaz, F.; Celiker, H. (Sage Publications Ltd, 2009)
Malnutrition is fairly common in end-stage renal disease (ESRD) patients, persistent lack of appetite being a major symptom. Ghrelin and obestatin are two hormones that are involved in appetite and energy homeostasis. The present study examined ghrelin and obestatin levels in 24 ESRD patients undergoing haemodialysis and 24 age-matched healthy controls. Serum and saliva ghrelin and obestatin levels in the ESRD patients were significantly higher compared with controls, while saliva ghrelin and obestatin levels in all study participants were significantly higher than serum levels. Saliva ghrelin correlated with serum ghrelin and saliva obestatin correlated with serum obestatin in all study participants, although there was no correlation between ghrelin and obestatin levels. In conclusion, the results suggest that the kidneys may have a role in the metabolism and/or clearance of obestatin, as they do for ghrelin. Further studies are needed to determine if elevated levels of these hormones in ESRD patients contribute to the malnutrition that is common in these patients.
Keywords: END-STAGE RENAL DISEASE; NUTRITION-REGULATING HORMONES; GHRELIN; OBESTATIN